Gut Microbiota Features Associated With Campylobacter Burden and Postnatal Linear Growth Deficits in a Peruvian Birth Cohort. (17th September 2019) - Rouhani, Saba; Griffin, Nicholas W; Yori, Pablo Peñataro; Olortegui, Maribel Paredes; Siguas Salas, Mery; Rengifo Trigoso, Dixner; Moulton, Lawrence H; Houpt, Eric R; Barratt, Michael J; Kosek, Margaret N; Gordon, Jeffrey I
Abstract: Background: Campylobacter infection is associated with impaired growth of children, even in the absence of symptoms. To examine the underlying mechanisms, we evaluated associations between Campylobacter infection, linear growth, and fecal microbial community features in a prospective birth cohort of 271 children with a high burden of diarrhea and stunting in the Amazonian lowlands of Peru. Methods: Campylobacter was identified using a broadly reactive, genus-specific enzyme-linked immunosorbent assay. 16S rRNA-based analyses were used to identify bacterial taxa in fecal samples at ages 6, 12, 18, and 24 months (N = 928). Associations between infection, growth, and gut microbial community composition were investigated using multiple linear regression adjusting for within-child correlations, age, and breastfeeding. Indicator species analyses identified taxa specifically associated with Campylobacter burden. Results: Ninety-three percent (251) of children had Campylobacter present in asymptomatic fecal samples during the follow-up period. A 10% increase in the proportion of stools infected was associated with mean reductions of 0.02 length-for-age z scores (LAZ) at 3, 6, and 9 months thereafter ( P < .01). We identified 13 bacterial taxa indicative of cumulative Campylobacter burden and 14 taxa significantly associated with high or low burden of enteroaggregative Escherichia coli, norovirus, or Giardia . Conclusions: Campylobacter infection is common in this cohort and associated with changes in microbial community composition. These results support the notion that disruptions to the fecal microbiota may help explain the observed effects of asymptomatic infections on growth in early life. Abstract : In this longitudinal cohort study, we demonstrate a high prevalence of asymptomatic Campylobacter infection among children aged 0–24 months, describe the effects of Campylobacter on gut microbial community composition, and link alterations in community composition to deficits in linear growth in early life.